Noise in a Neonatal Intensive Care Unit: Exploring Its State and Solutions. (30th December 2022) - Sabetsarvestani, Raheleh; Köse, Semra; Geçkil, Emine; Tosun, Esra Ertürk; Tokan Özkılıçaslan, Fatma; Karaarslan, Fatih; Altunhan, Hüseyin
Abstract : Background: Concerns regarding the environmental noise issue in neonatal units and an interest in developing strategies to reduce this noise have motivated researchers to conduct comprehensive qualitative research to elucidate the current situation and help improve it. Purpose: This study aims to explore the current state of noise and possible solutions in a neonatal intensive care unit (NICU) in Konya, Turkey. Methods: In 2021, a descriptive exploratory study was conducted with a qualitative content analysis approach. Eighteen nurses, three physicians, seven staff members, and four mothers were selected to participate in the study via purposeful sampling. The data were collected from two semi-structured interviews, six focus groups, six observations, and sound source level measurements using a sound decibel meter. Qualitative content analysis was used to analyze the data. Results: Three main themes and seven major categories emerged from the data analysis. The themes were overt and covert sources, pan-negative effects, and holistic modification . All recorded sound levels exceeded the recommended noise level of 45 dB. Fifty-seven percent of sound sources were in the range of 45–65 dB, and 43% were higher than 65 dB. Implications for Practice and Research: This study showed that NICU has a noisy environment with hidden sound sources that can negatively affect all people. This situation must be approached seriously by holistic modification involving environmental modification, behavioral modification, and resource management. It highlighted that each environment is unique and needs to be carefully evaluated to find a suitable and cost-effective solution.